Dendrite balconies - Braune, Sean, 1985- (Brave & brilliant series ;, 2019)
"Text surrounds us. Text is everywhere, all the time, and the contemporary world is a codex to be deciphered and disassembled. In Dendrite Balconies, Sean Braune harvests the language that surrounds us--pieces and shards from other writers, conversations, and popular media--reassembling textual fragments into poetic sculptures. Blending together conceptual writing and lyric poetry, Braune locates beauty in the chaotic landscape of the urban environment and the digital era. Full of smart, funny, insightful moments, this is a poetic montage that collapses experimental traditions into the noise and clang of urban space, and out of the silent cries of canons and libraries. When the author dies, the reader is born. In Dendrite Balconies, the reader becomes a new author as Braune assembles frenetic, dissociative fragments of language into an aesthetic and sonic whole."--